MARINA TSVETAEVA AS A CULTURAL FIGURE IN THE LITERARY WORKS OF BILJANA JOVANOVIĆ AND IRENA VRKLJAN - Sonja Veselinović (Filolog, 2025)
This paper presents the early reception of Marina Tsvetaeva's poetry, prose, and essays in Yugoslav, or more specifically, Serbian translated literature, with the intention to examine the influence of the Russian poet as an exemplary cultural figure in the works of Yugoslav women writers. As a cultural icon, Tsvetaeva is present in the literary oeuvre of Serbian writer Biljana Jovanović (1953‒1996), from her second novel, Dogs and Others, to her last play, A Room on the Bosphorus, where she appears as one of the characters. Presenting Tsvetaeva as a countercultural figure, Jovanović builds her authorial authority and integrity based on the example of the Russian author's poetic persona and her autobiographical writing. However, she also establishes a reciprocal relationship, paying homage to this influential poet who, during her lifetime, was deprived of adequate attention from readers and critics. This aspect is also highly relevant in the work Marina, or About Biography by Croatian author Irena Vrkljan (1930‒2021), especially in the frame of the reception of Tsvetaeva's autobiographical works. By juxtaposing details from Tsvetaeva's biography with her own, Vrkljan legitimizes her poetic confrontation with genre, social, and gender conventions. In both writers' works, Tsvetaeva appears as a privileged interlocutor and a desired reader, in contrast to the presumed critical reaction of the literary establishment.